Potassium leaching from millet straw as affected by rainfall and potassium rates - Rosolem, Ciro Antonio [UNESP]; Calonego, Juliano Carlos [UNESP]; Foloni, José S. S. [UNESP] (Taylor & Francis, 2005)
Pearl millet (Penisetum glaucum) is an interesting species to be used as cover crop in tropical areas, showing a high ability in potassium uptake. Potassium (K) is not linked to organic compounds in the plant, and can easily be released from decaying straw becoming available for subsequent crops. This experiment evaluated K leaching from millet straw grown under potassium rates (0, 100, 200, and 300 mg dm-3), and submitted to five levels of simulated rain (5, 10, 20, 40, and 80 mm). Plants were grown in soil filled pots in a greenhouse. On the 50th day after emergence, the plants were desiccated with glyphosate. Artificial rain was applied over the straw. Potassium deficiency speeds up millet dehydration after herbicide application and increases lightly rain water retention in the straw. The amount of K leached right after plant desiccation is correlated with the residue nutrient content and can be as high as 64 kg ha-1 considering a mulch of 8 t ha -1. Although well-nourished millet plants release considerable amounts of K with the first rains, a large percentage of the nutrient is still retained in the straw. Copyright © Taylor & Francis, Inc.
Keywords: Cover crops; K fertilization; Nutrient cycling; cover crop; leaching; potassium; Penisetum; Penisetum glaucum; Pennisetum glaucum